Rewilding with invertebrates and microbes to restore ecosystems: Present trends and future directions. Issue 12 (2nd May 2021) - Contos, Peter; Wood, Jennifer L.; Murphy, Nicholas P.; Gibb, Heloise
Abstract: Restoration ecology has historically focused on reconstructing communities of highly visible taxa while less visible taxa, such as invertebrates and microbes, are ignored. This is problematic as invertebrates and microbes make up the vast bulk of biodiversity and drive many key ecosystem processes, yet they are rarely actively reintroduced following restoration, potentially limiting ecosystem function and biodiversity in these areas. In this review, we discuss the current (limited) incorporation of invertebrates and microbes in restoration and rewilding projects. We argue that these groups should be actively rewilded during restoration to improve biodiversity, ecosystem function outcomes, and highlight how they can be used to greater effect in the future. For example, invertebrates and microbes are easily manipulated, meaning whole communities can potentially be rewilded through habitat transplants in a practice that we refer to as "whole‐of‐community" rewilding. We provide a framework for whole‐of‐community rewilding and describe empirical case studies as practical applications of this under‐researched restoration tool that land managers can use to improve restoration outcomes. We hope this new perspective on whole‐of‐community restoration will promote applied research into restoration that incorporates all biota, irrespective of size, while also enabling a better understanding of fundamental ecological theory, such as colonization and competition trade‐offs. This may be a necessary consideration as invertebrates that are important in providing ecosystem services are declining globally; targeting invertebrate communities during restoration may be crucial in stemming this decline. Abstract : Restoration and rewilding projects have historically overlooked the role played by invertebrates and microbes in restoring ecosystems. Here, we review the current state of microbial and invertebrate rewilding projects and provide recommendations on how projects can move forward in the future.